A Health Economic Evaluation of the World Health Organization Surgical Safety Checklist: A Single Center Assessment. Issue 4 (14th April 2022) - Healey, Andy; Søfteland, Eirik; Harthug, Stig; Haaverstad, Rune; Mahesparan, Rupavathana; Hjallen, Bjørg Merete; Eide, Geir Egil; Sevdalis, Nick; Haugen, Arvid Steinar
Abstract : Objectives: To evaluate cost-effectiveness of the WHO Surgical Safety Checklist. Background: The clinical effectiveness of surgical checklists is largely understood. Few studies to-date have evaluated the cost-effectiveness of checklist use. Methods: An economic evaluation was carried out using data from the only available randomized controlled trial of the checklist. Analyses were based on 3702 procedures. Costs considered included checklist implementation costs and length and cost of hospital stay, costs of warming blanket use, blood transfusions and antibiotics used in the operating room, and the cost of clinical time in the operating room – all calculated for each procedure and its associated admission. Nonparametric bootstrapping was used to simulate an empirical distribution of the mean effect of the checklist on total admission costs and the probability of observing a complication-free admission and to quantify sampling uncertainty around mean cost estimates. Results: The overall cost of checklist implementation was calculated to be $900 per 100 admissions. Implementation of the WHO checklist resulted in an additional 5.9 complication-free admissions per 100 admissions and an average of 110 bed-days saved per 100 admissions. Accounting for all costs included in the analysis, for every 100 admissions, use of the WHO checklist was estimated to save $55, 899. Conclusions: Implementation of the WHO checklist was a cost-effective strategy for improving surgical safety.